Psychosocial interventions for pain management in advanced cancer patients: a systematic review and meta-analysis - Warth, Marco; Zöller, Joshua; Köhler, Friederike; Aguilar-Raab, Corina; Keßler, Jens; Ditzen, Beate (Current oncology reports, 2020)
This systematic review and meta-analysis aimed to synthesize the evidence on the effects of psychosocial interventions on pain in advanced cancer patients.